Voicing the supernatural in Anglo-Saxon England - Coker, M (2019)
‘Voicing the Supernatural in Anglo-Saxon England’ is a study of the representation of supernatural voices in Anglo-Saxon literature, with a special emphasis on Old English poetry. Focusing primarily on representations of the direct discourse of supernatural characters, especially when, how, and why these characters’ voices are represented with unique stylistic features, the aim of this dissertation is twofold: a) to understand what representations of supernatural discourse can teach us about how Anglo-Saxon verbal artists perceived and interacted with the supernatural; and b) how these representations might inform our understanding of Anglo-Saxon poetic style and of the cultural roles of poetry in Anglo-Saxon society. In five chapters, ‘Voicing the Supernatural’ incorporates stylistic analysis of direct speech in six Old English poems: Solomon and Saturn I, The Phoenix, Soul and Body I, The Dream of the Rood, Guthlac A, and Genesis A, grounding these analyses in extensive research into their artistic, religious, and social contexts and incorporating Old English and Anglo-Latin poetry and prose as well as ecclesiastical, Germanic, Celtic, and classical sources and analogues. ‘Voicing the Supernatural’ argues that as poets translated their subject matter into the Old English poetic medium, they left traces of important historical conceptions about spirituality and poetry: for example, the consistent association between hypermetric lines and divine discourse observed in this dissertation throws into relief the genealogical relationship thought to exist between Old English hypermetric lines and Old Norse ljóðaháttr verse, which is primarily used for mythological and gnomic poems.